2017
DOI: 10.11646/zootaxa.4227.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Type Localities of Heteroptera (Insecta: Hemiptera) from Turkey

Abstract: The Heteroptera (Hemiptera) fauna of the Palaearctic Region is represented by 9365 species belonging to 1632 genera of which 1349 species belonging to 469 genera are also recorded from Turkey. Type localities of 237 species are in Turkey of which 108 species and 4 subspecies are endemic for the Heteroptera fauna of Turkey, indicating the importance of the country as a refugium, genetic hotspot and dispersal centre during pleistocene glaciation. Some heteroptera are important in agriculture as predators used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 673 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…As a result of this study, a total of 36 species of Psallus are confirmed to occur in Turkey, as detailed in the following updated checklist (see Kerzhner and Josifov 1999, Lodos et al 2003, Önder et al 2006, Konstantinov and Namyatova 2008, Matocq and Pluot-Sigwalt 2011, Aukema et al 2013, Matocq et al 2014, Dursun and Fent 2017, Çerçi and Koçak 2017). An E* indicates the species endemic for the country; non-endemic species are followed by a reference for Turkey.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…As a result of this study, a total of 36 species of Psallus are confirmed to occur in Turkey, as detailed in the following updated checklist (see Kerzhner and Josifov 1999, Lodos et al 2003, Önder et al 2006, Konstantinov and Namyatova 2008, Matocq and Pluot-Sigwalt 2011, Aukema et al 2013, Matocq et al 2014, Dursun and Fent 2017, Çerçi and Koçak 2017). An E* indicates the species endemic for the country; non-endemic species are followed by a reference for Turkey.…”
Section: Discussionmentioning
confidence: 69%
“…In Turkey, 12 of a total of 36 species are endemic, with a percentage of 33.3 %. With the exception of Psallus (Phylidea) quercicola (Reuter, 1904), known also from the European part of Turkey, all Turkish endemic species of Psallus are known only from Anatolia (Seidenstücker 1959, 1962, 1966a,b, 1972; Linnavuori 1994; Lodos et al 2003; Önder et al 2006; Konstantinov and Namyatova 2008; Matocq and Pluot-Sigwalt 2011; Matocq et al 2014; Dursun and Fent 2017). Moreover, one species, Psallusdionysos Simon & Strauss, 2014, is endemic to the Greek island of Lesbos, divided only by a narrow strait from the western coast of Anatolia (Simon and Strauss 2014) and another, Psallus (Apocremnus) cyprius Wagner, 1977, is endemic to Cyprus, not far from the southern coast of Anatolia (Linnavuori 1994).…”
Section: Checklist Of Psallus From Turkeymentioning
confidence: 99%
“…In the south, the eastern part of the Taurus mountain range separates the dry hot steppe and desert Southeastern Anatolia from the cold-arid Eastern Anatolia, the western part separates the Mediterranean coastal region, which has a typical Mediterranean climate, from the arid steppe form Central Anatolia. There are also several volcanic mountains in Central and Eastern Anatolia (Demirsoy 2002, Dursun & Fent 2017.…”
Section: Introductionmentioning
confidence: 99%
“…The same geological formations support the formation of endemic species by forming barriers in the south and north of Anatolia. Another reason for the species diversity is that during the Quaternar glaciation, important refugee areas in Anatolia and Thrace regions were not affected by the glaciation and formed a shelter for organisms (Dönmez 1968, Demirsoy 2002, Dursun & Fent 2017.…”
Section: Introductionmentioning
confidence: 99%
“…It has been known to possess a rich fauna of Hereroptera. Thus, some faunistic and systematic studies about the Heteroptera have been conducted by both foreign and native researchers in Turkey (Dursun 2011a, 2011b, Dursun and Fent 2010, 2011a, 2011b, 2017, Dursun and Salur 2013, Fent et al 2010a, 2010b, Kaçar and Dursun 2015, Lodos et al 1978, 1998, 1999, Önder et al 2006, Reuter 1881, 1882, 1896, 1909, Seidenstücker 1963a, 1963b, 1963c, 1964, 1965, 1966a, 1966b, 1967. Yet, such a study is essential for researchers who are interested in Heteropterans as aphids predatory in West Palaearctic region including Turkey.…”
mentioning
confidence: 99%